Dynamic operating reserve procurement improves scarcity pricing in PJM. (December 2020) - Lavin, Luke; Murphy, Sinnott; Sergi, Brian; Apt, Jay
Abstract: Competitive electricity markets can procure reserve generation through a market in which the demand for reserves is administratively established. A downward sloping or stepped administrative demand curve is commonly termed an operating reserve demand curve (ORDC). We propose a dynamic formulation of an ORDC with generator forced outage probabilities conditional on ambient temperature to implement scarcity pricing in a wholesale electricity market. This formulation improves on common existing methods used by wholesale market operators to articulate ORDCs by explicitly accounting for a large source of observed variability in generator forced outages, whereby for a fixed load, more reserves are required during times of extreme heat and cold to maintain a constant risk of reserve shortage. Such a dynamic ORDC increases social welfare by 17.1 million compared to current practice in the PJM Interconnection during a high load week in a welfare-maximizing electricity market with co-optimized procurement of energy and reserves. A dynamic ORDC increases reserve prices under scarcity conditions, but has minimal effects on total market payments. The results are directly relevant to the modeled two-settlement electricity market in PJM, which is currently undergoing enhancements to its ORDC. Highlights: Conditioning outages on temperature improves operating reserve demand curves. Generators realize benefits through increased reserve prices. Consumers realize benefits through reduced loss-of-load probability. Dynamic reserve procurement can be implemented in existing electricity market.